2014
DOI: 10.1017/s0007114514002943
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota of humans, dogs and cats: current knowledge and future opportunities and challenges

Abstract: High-throughput DNA sequencing techniques allow for the identification and characterisation of microbes and their genes (microbiome). Using these new techniques, microbial populations in several niches of the human body, including the oral and nasal cavities, skin, urogenital tract and gastrointestinal tract, have been described recently. Very little data on the microbiome of companion animals exist, and most of the data have been derived from the analysis of the faeces of healthy laboratory animals. High-thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
153
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(174 citation statements)
references
References 77 publications
17
153
1
3
Order By: Relevance
“…However, little is known on how the dietary protein-to-carbohydrate ratio influences gut microbiotas in dogs. The five predominant bacterial phyla reported in this study, Fusobacteria , Firmicutes , Bacteroidetes , Actinobacteria , and Proteobacteria , were similar to those in previous reports (2729), but relative abundances of each phyla can vary from study to study and likely arise from factors such as breed, sex, age, diet, or even different sampling or sequencing methodologies (27). In this study, we observed that evenness but not richness increased in response to diet manipulation; that is, the abundances of taxa present became more equal rather than community members that may have been undetected in phase 1 expanding in growth.…”
Section: Discussionsupporting
confidence: 88%
“…However, little is known on how the dietary protein-to-carbohydrate ratio influences gut microbiotas in dogs. The five predominant bacterial phyla reported in this study, Fusobacteria , Firmicutes , Bacteroidetes , Actinobacteria , and Proteobacteria , were similar to those in previous reports (2729), but relative abundances of each phyla can vary from study to study and likely arise from factors such as breed, sex, age, diet, or even different sampling or sequencing methodologies (27). In this study, we observed that evenness but not richness increased in response to diet manipulation; that is, the abundances of taxa present became more equal rather than community members that may have been undetected in phase 1 expanding in growth.…”
Section: Discussionsupporting
confidence: 88%
“…Gross energy (kJ/g) was determined using bomb calorimetry. Crude fibre was determined using the gravimetric method (AOAC 978.10) and nitrogen-free extractable matter (NFE) by difference (Deng & Swanson, 2015). Dry matter (DM) was calculated as 100 less the % moisture.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with this, over the last five years much of the research in companion animal nutrition has focussed on understanding the role of diet on the composition of the faecal microbiota (Deng & Swanson, 2015). To date, diet-induced changes in faecal microbiota observed in humans and rodents have been extrapolated to dogs and cats, in spite of their very different dietary requirements.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The gastrointestinal tract of dog is a complex microbial ecosystem that mainly consists of bacteria, methanogenic archaea, yeasts, moulds and viruses (Deng and Swanson, 2015). Enterobacteriaceae was indeed the most important family of gut microbiota, causing well-defined diseases like gastroenteritis, septicaemia, reproductive and urinary tract infections (Suchodolski, 2011).…”
Section: Introductionmentioning
confidence: 99%